Peningkatan Hasil Belajar Matematika melalui Penerapan Model Pembelajaran Jigsaw pada Siswa MTs Negeri 1 Indramayu - Nani Widuriatni (Jurnal Pendidikan Madrasah, 2021)
This research aims to improve the quality of the learning process of Mathematics subjects through jigsaw learning models. This research was conducted at MTs Negeri 1 Indramayu Year of Study 2019/2020 with the research subjects of class VIII students. This study using the Class Action Research (PTK) method was conducted in 2 cycles. The results showed that the application of jigsaw learning models can improve student learning achievement both in terms of classical completion of student learning, shown in cycle I by 68%, increased to 100% in cycle II. Students' learning activity levels also increased from 3.1 with moderately active categories in cycle I to 4.1 with active categories showing a 10% increase. Jigsaw learning models can be applied to MTs students to improve the learning outcomes of math subjects.